Mathematics Learning Strategies for Students With Severe Autism - Nadia Rusdaini; T. Tutut Widiastuti, A; Wildatus Sholihah (Gunung Djati Conference Series, 2022)
The purpose of this study was to determine the appropriate mathematics learning strategy for students with a diagnosis of severe autism. This research uses the literature study method, in the literature study the author uses various written sources such as articles, journals, and documents that are relevant to the research conducted. Literature studies are used to study reading sources so that they can provide information related to the problem being studied by the researcher. The results showed that an effective strategy in learning mathematics for students with severe autism was visual-based learning. This can be conveyed through mathematics learning media, one of which is teaching aids. The accompanying teacher also plays an important role in this, the accompanying teacher should teach using simplified materials and emphasize an individual approach to each student and also apply teaching methods by repetition.